Peningkatan Kemampuan Ibu Tentang Pengetahuan Treatment Preventif (Pijat) Pada Bayi Di Kelurahan Sawah Lebar Baru Kecamatan Ratu Agung Kota Bengkulu - Ronalen Br. Situmorang; Eko Hardiyanto; Syami Yulianti (Jurnal Dehasen Untuk Negeri, 2022)
Increased mother's ability about knowledge of preventive treatment (massage) in children. Babies can be useful for stimulating motor nerves, improving sleep patterns, aids digestion and promotes emotional calm in babies serves to save babies from bad sleep patterns, especially in Infants in Sawah Lebar Baru Village, Ratu Agung Kota Sub-district. Bengkulu in order to increase knowledge about massage in infants and children can be of good use without harming the baby's health in life recently. This community service is aimed at mothers who have Baby in Sawah Lebar Baru Village, Ratu Agung District, Bengkulu City which is still active. The purpose of this community service is to determine the extent of mother's knowledge about preventive treatment (massage) Baby to increase knowledge about Baby massage to maintain freshness, health and fitness in Babies and can increase Generations Hope of the Nation and the State for the future. Based on the results of community service in the Sawah Lebar Baru Village, Ratu Agung Subdistrict, Bengkulu City, the level of knowledge of mothers who have babies about preventive treatment (massage) in infants in the Good category is 9 respondents (60%), in the poor category as many as 6 respondents (40% ). So it can be concluded that the level of knowledge of mothers who have babies about preventive treatment (massage) in infants is mostly in the Good category as many as 9 respondents (60%).